STRUCTURAL ANALYSIS OF THE COSTS AND THEIR EFFICIENCY INMARITSA-IZTOK 2 TPP EAD FOR THE PERIOD 2013-2022. - Kolev, Rosen (E-Journal VFU, 2024)
The energy crisis on a global scale due to both the economic difficultiescaused by COVID-19 and the lack of resources related to the war in Ukraine has led to ashortage of electricity in the European free markets. Restrictions related to the Kyoto documentand environmental pollution imposed in the European Union predetermine the closure of anumber of coal plants. The economic situation in the last two years has shown that neither155globally nor at the European level are industries ready to abandon the use of electricity fromsources that pollute the environment. The production of electricity in Bulgaria is highlydependent on thermal power plants, and they have been producing and placing record amountsof electricity on the free markets in recent years. An attempt has been made to highlight theimportance of TPP "Maritsa-Iztok 2" EAD for the energy balance and national security in theRepublic of Bulgaria.
Keywords: CVP analysis; management accounting; electricity; analysis; efficiency; cost